Factores asociados a síntomas depresivos en trabajadoras sexuales - Bohórquez, Ingrid Mercedes (2010)
Introduction: The working conditions and violence against sex workers has been linked to increasing rates of sexual transmitted diseases. But there are also other diseases that affect their mental health. Objectives: To determine the magnitude of depressive symptoms and associated factors in sex workers. Design: Crossanalytic study. Setting: Health Centre of reference for the prevention and control of sexually transmitted infections. Participants: Sex workers. Interventions: Beck test was applied to 117 sex workers attended between May and June 2010 in order to measure depressive symptoms as well as a survey to determine socio-demographic and social (physical abuse, psychological and sexual labor and harmful habits: alcohol and drug abuse) factors, risky sexual behavior and job characteristics (age at onset, years of work, job satisfaction). Main outcome measures: Percentage of depressive symptoms and weight of association between factors and presence of depressive symptoms. Results: Some level of depressive symptoms was found in 56,4% of sex workers. Severe depressive symptoms were present in 23,9%. Main factor associated with depression was background of frequent physical abuse (OR = 9,46, CI95%: 1,05 to 85,07; p = 0,045). Factors associated with severe depressive symptoms were income less than S/. 1 000.00, having children, having started sex work before age 18, and drug abuse (p <0,05). Conclusions: Over 50% of sex workers had some level of depressive symptoms generally associated with history of physical abuse. Severe depressive symptoms were associated to income less than S/. 1 000.00, having children, having started sex work before age 18, and drug abuse.